Functional analysis of box I mutations in yeast site-specific recombinases Flp and R: pairwise complementation with recombinase variants lacking the active-site tyrosine. - Chen, J W (1992)
The site-specific recombinases Flp and R from Saccharomyces cerevisiae and Zygosaccharomyces rouxii, respectively, are related proteins that belong to the yeast family of site-specific recombinases. They share approximately 30% amino acid matches and exhibit a common reaction mechanism that appears to be conserved within the larger integrase family of site-specific recombinases. Two regions of the proteins, designated box I and box II, also harbor a significantly high degree of homology at the nucleotide sequence level. We have analyzed the properties of Flp and R variants carrying point mutations within the box I segment in substrate-binding, DNA cleavage, and full-site and half-site strand transfer reactions. All mutations abolish or seriously diminish recombinase function either at the substrate-binding step or at the catalytic steps of strand cleavage or strand transfer. Of particular interest are mutations of Arg-191 of Flp and R, residues which correspond to one of the two invariant arginine residues of the integrase family. These variant proteins bind substrate with affinities comparable to those of the corresponding wild-type recombinases. Among the binding-competent variants, only Flp(R191K) is capable of efficient substrate cleavage in a full recombination target. However, this protein does not cleave a half recombination site and fails to complete strand exchange in a full site. Strikingly, the Arg-191 mutants of Flp and R can be rescued in half-site strand transfer reactions by a second point mutant of the corresponding recombinase that lacks its active-site tyrosine (Tyr-343). Similarly, Flp and R variants of Cys-189 and Flp variants at Asp-194 and Asp-199 can also be complemented by the corresponding Tyr-343-to-phenylalanine recombinase mutant.